Evaluation of Herbicidal Potential of Eucalyptus spp for Biological Control of Dactyloctenium aegyptium L. - Ehtaiwesh, Amal (Journal of Pure & Applied Sciences, 2021)
Pots culture experiment was conducted to evaluates the herbicidal potential of Eucalyptus spp. (aceae) on growth of Dactyloctenium aegyptium L. (Poaceae). Leaves extract with concentrations of 10, 20 and 40% of Eucalyptus plant were applied as soil and foliar application to seeds and seedlings of D. aegyptium species. The result indicated that the application of Eucalyptus leaves extracts caused significant reduction in germination traits, root and shoot length, seedling fresh and dry weights. Also, the result revealed that the Inhibitory effect of Eucalyptus extract on D. aegyptium L was more noticeable in plant growth traits than on germination traits. Results show that among the different concentration of Eucalyptus leave extracts used in this study, 40% was the most toxic and caused the significant effect on germination and growth traits of Dactyloctenium aegyptium. Application of 40% of Eucalyptus leave extract decreased germination percentage by 30%, mean daily germination by 45%, shoot length by 38%. root length by 54%, number of branches by 61%, number of leavesby59%, seedling fresh weights by 23%, seedling dry weights by 62% and seedling vigor index by 60%. The results of this study concluded that the use of Eucalyptus plants have the potential to be developed further as a bio-herbicide system to control weed such as Dactyloctenium aegyptium L. However, more researches are needed to evaluate the negative impact of Eucalyptus on crop growth.